Characterization of essential oil profiles, triterpenic acids, and biological assay in aerial parts of various Thymus persicus Jalas (Ronniger ex Rech.f.) populations - Ziba Bakhtiar; Mohammad Hossein Mirjalili; Mohammad Selseleh; Alireza Yavari; Mansour Ghorbanpour (Chemical and Biological Technologies in Agriculture, 2023)
Abstract Thymus persicus is a valuable natural source of anticancer triterpenic acids (TAs) such as betulinic acid (BA), oleanolic acid (OA), and ursolic acid (UA), which is growing wild in the northwest of Iran. In the present study, variability in morphological characteristics, phytochemical composition, and biological activity among T. persicus populations (TPPs) were investigated. The plants were phenotypically different with the highest variations in some morphological traits. In total, sixty-seven compounds representing 97.2‒99.9% of the essential oils were identified. Thymol (8.1‒43.9%), α-terpineol (1.8‒34.2%), and p-cymene (0.4‒13.4%) were the major components of the studied oils. The content of BA, OA, and UA was ranged as 530.55 ± 13.04‒856.89 ± 6.76, 419.35 ± 11.44‒584.43 ± 12.67, and 941.66 ± 11.49‒1070.82 ± 10.14 mg 100 g‒1 DW in the studied TPPs, respectively. The highest total phenol content (87.26 ± 4.35 mg GAE g–1 DW), total flavonoid content (72.34 ± 2.63 mg QE g–1 DW), and antioxidant property (IC50 = 64.28 ± 4.57 μg ml–1 and 61.68 ± 1.10 μmol Fe+2 g–1 DW) were recorded in TPP1 (Baderlu). The essential oil of the TPP3 (Angooran) showed the lowest minimal inhibitory concentration (MIC) against the bacteria (0.005‒0.080 mg ml–1) and fungi (0.077‒0.100 mg ml–1) among the studied TPPs. Multiple regression analysis showed an associated correlation among morphological, phytochemical characteristics, and biological activities. Canonical correspondence analysis also determined relationship between phytochemical traits and environmental factors. These findings contain valuable data for the conservation and sustainable exploitation of this valuable medicinal plant. Graphical Abstract